2021
DOI: 10.3390/educsci11080447
|View full text |Cite
|
Sign up to set email alerts
|

Internship of Accounting Students in the Form of E-Learning: Insights from Poland

Abstract: The COVID-19 pandemic has imposed on us not only e-learning with higher education providers, but also triggered considerable difficulties in organization internships. Institutions and enterprises that used to be eager to take interns have refused to do so. In these conditions, the key objective for the Faculty of Management at the UTP University in Bydgoszcz was to organize e-internships to ensure a working environment similar to the real working conditions of the accounting department. A new internship progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
1
10
0
2
Order By: Relevance
“…In order to let their students have zero contact with the job as much as possible, the institutions have reformed the teaching system of accounting profession one after another, combining theoretical teaching with practice and requiring students to have at least half a year of on-the-job internship [5]. Although it is said that the internship is very important in the teaching system, the accounting talents who can really adapt to the development needs of society and enterprises are not produced in large quantities [6]. All these problems exist which a ect the e ect and quality of on-the-job internship of accounting students in colleges and universities and many students of accounting majors.…”
Section: Introductionmentioning
confidence: 99%
“…In order to let their students have zero contact with the job as much as possible, the institutions have reformed the teaching system of accounting profession one after another, combining theoretical teaching with practice and requiring students to have at least half a year of on-the-job internship [5]. Although it is said that the internship is very important in the teaching system, the accounting talents who can really adapt to the development needs of society and enterprises are not produced in large quantities [6]. All these problems exist which a ect the e ect and quality of on-the-job internship of accounting students in colleges and universities and many students of accounting majors.…”
Section: Introductionmentioning
confidence: 99%
“…During the teaching process, it is possible to observe several phases: motivational (preparation of students for active learning), exposure (initial acquaintance of students with the new curriculum), fixation (initial repetition and confirmation of the curriculum), and diagnostic (testing of acquired knowledge, skills, and habits). Research on the impact of a pandemic on education is currently addressed by several authors and institutions within their conditions, for example [4][5][6][7][8][9][10][11].…”
mentioning
confidence: 99%
“… Gill (2020) explored the employability skills possessed by Australian students who had undertaken online WP and confirmed that they had become accustomed to remote working, which would be beneficial for future positions that might include this kind of working. Januszewski and Grzeszczak (2021) found that students appreciated the online WP programme and that it effectively improved their self-learning and ability to performing tasks independently. In contrast to those three studies, Hora et al (2021) found a negative effect of online WP – in comparison to students undertaking an in-person WP, online interns had significantly lower levels of happiness with their experience, poorer scores for both academic and developmental assessments, lower levels of learning of 21st-century skills, and less expansion of professional networks.…”
Section: Literature Reviewmentioning
confidence: 98%